AFCP French Total Ankle Replacement Registry: Activity Report of First 3 Years. Issue 1 (19th August 2016) - Besse, Jean-Luc; Ferre, Bruno; ,
Category: Ankle Arthritis Introduction/Purpose: In 2015-2016, renewal of the 5-yearly French health insurance financing of TAR requires exhaustive data. The French Foot Surgery Society (AFCP – project initiator and promoter), Lyon University Hospitals Clinical Research Unit (administrator and scientific manager) and manufacturers (operational financers) therefore launched a national TAR registry on June 18, 2012 (CNIL data protection approval). For each TAR, there are 3 forms: prosthesis patient data, reoperation, monitoring (optional).We present results for the first 3 years. Methods: Under the 3-party contract, manufacturers pay for 6-monthly reports and €32 per prosthesis to cover the reminder procedure (each company gives the Research Unit a monthly list of surgeons, and the Unit sends out 3 reminders to those who have not entered data). Every surgeon implanting TARs must file a pre-registration formula on the website; after verification, the administrator sends the center number and personal login. Registration takes 3-5 minutes; implant ID number is automatically provided after complete data input. Then surgeons distribute a legal information sheet plus passport (patients can alert the research unit directly in case of re-operation). From June 2012 to June 2015, 1276 of the 1, 612TARs implanted in France were registered (79.2%): 514 Salto, 353 SaltoTalaris, 307 Hintegra, 81 Star, 21 Akile. 202 centers implanted TARs: 127 registered TARs in the Registry, 75 registered none. Ten centers registered more than 30 (737 TARs), and 36 only one; surgeon investment was proportional to number of TARs (41% registration rate in centers registering one TAR to 94% in centers registering more than 10 TARs). Results: Mean age at implantation was 63.4 years (18-91 years); etiology was mainly post-traumatic (49%), osteoarthritis on laxity (19%), primary (17%) or inflammatory (7%), with some hindfoot misalignment (21% varus >5°, 11% valgus >5°). Surgery comprised: 97% standard implants (MB thickness mainly 4 mm (26%) or 5 mm (25%)); tourniquet time, 89 min; malleolar fracture, 6.4%; associated Achilles lengthening, 20.9%; ligament plasty, 8.6%; osteotomy, 4.9%; arthrodesis, 2.3%. 528 patients (41.4%) had at least 1 follow-up form (wound healing delay 6.8%, infection 0.7%, DF 9.9°, PF 22.1°). At 3 years, 74 patients (5.8%) were reoperated on (17 patients (2%) at 2 yrs): i.e. 89 reoperations (1-4/patient). 51 patients (4%) had revision without implant removal (arthrolysis 33%, complementary osteotomy 11.5%, Achilles lengthening 9.8%, ligament plasty 6.6%, etc); 9 (0.7%) with partial TAR change (tibia 6 – talus 3); 14 (1.1%) with TAR removal (4 re-do TAR, 8 arthrodesis, 2 temporary spacer before arthrodesis). Conclusion: Follow-up was insufficient to assess survival. This registry procedure, closely followed by the health authorities, has overcome French surgeons' aversion for registries (exhaustiveness 2% for French Hip registry). Exhaustiveness could be improved if taken into account for surgeons' accreditation. But an independent annual telephone audit requested by HAS (French Health Authority) showed that at 1 year the registry detected only 29% of reoperations vs phone call survey of registry patients: registries are not the gold standard and probably overestimate the real survival rate.